Pemberdayaan Warga Binaan Melalui Kegiatan Pelatihan di Rumah Tahanan Negara Kelas IIB Kota Sawahlunto - Fadila, Fauzan; Ismaniar, Ismaniar (Penerbit Aksara Rentaka Siar (ARS), 2020)
This research is motivated by the empowerment of fostered citizens through skills training activities in the Class IIB Detention Center of Sawahlunto City. This type of research is qualitative research with a case study method. Data collection techniques used were observation, interviews, and documentation. Qualitative data analysis used is data reduction, data presentation, and drawing conclusions. From the results of the study it was found that the training activities carried out aim to change the attitudes and behavior of fostered citizens for the better, provide a handle on capital skills that can be utilized when the sentence ends so that they have more positive activities and do not repeat the crimes they have committed, fill the day days during their sentence, and can change the public's bad view of the Detention Center. In the implementation of training activities the use of methods in accordance with the training carried out is the demonstration method and practice method. The material provided in this activity is material about welding, craft making and spiritual material which ultimately returns to the purpose of empowering the fostered citizens, namely changing the attitudes and behavior of the fostered citizens